Greece Financial Crises and Sukuk Markets: Experience From Gulf Countries - Aldrin Herwany; Erie Febrian; Imam Buchari (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
Many studies have been carried out to investigate the impact of recent European financial crises on the performance of financial instruments in other regions. Nevertheless, there have been insufficient studies explaining such impact on Islamic financial instrument. In particular, whether Greece Financial crises have affected performance of Sukuk traded in Gulf Markets needs to be answered. This study is aimed at empirically investigating the causality of credit and liquidity risk on Sukuk Markets in Gulf economies in the period of Greece Financial Crises. We analyzed the Sukuk data by employing Granger casuality test, with all the associated vector autoregression model procedures. Our findings show that Bahrain sukuk market is cointegrated with those of Qatar and UAE in the full period observation. Meanwhile, during the crisis, Qatar Sukuk market is cointegrated with those of UAE Bahrain. We also find that Bahrain Sukuk triggers market shock in both Qatar and UAE Sukuk markets. Bahrain consistently causes changes in price and spread of UAE Sukuk, both in the context of the full period and the during-crisis period.DOI: 10.15408/aiq.v9i1.3733